If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 7) = 0 Reorder the terms: (7 + x) = 0 Remove parenthesis around (7 + x) 7 + x = 0 Solving 7 + x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + x = 0 + -7 x = 0 + -7 Combine like terms: 0 + -7 = -7 x = -7 Simplifying x = -7
| 15b^2-65b-50=0 | | f(x)=(-7x+4)(x-3)(-6x+1) | | 3y+5=8y-13 | | 7=3a-5a-a+7 | | x/3-1= | | .7x=25000 | | 4(3x-5)=-50 | | 21s^2+43s+20=0 | | -0.51x-3.2=0.8+7.28 | | 1.15g+1.25g=15 | | 25y^2+49y-4=0 | | -7x+2y=-51 | | 18.5w+6.5w-2.8w=149.1 | | 3x-21x=0 | | 9-7y=2 | | 90x-5.4=391.4-38x | | 4n-2+7n=29 | | 5x+32=4+2x | | 4+14x^2-7x=0 | | 6b+6=-48 | | -7+8n=5+13n | | 10-1235=21 | | -21x^2-20x-4=0 | | 2x^3-50x+72=0 | | 2+2+1+1+7+3+2+4+1+4= | | 4(x-1)=1.2(x-8) | | 9+10x=.4 | | x^3+x^2-18x-54=0 | | 9+10x=.2 | | 10-29v+10v^2=0 | | 10-1+4+(-16)= | | -9.2-x=4.5 |